METHODS OF LEARNING IN PROCESS OF SPORTS TRAINING - Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Methods of learning the sports problems mean the appropriate technique of management with process, which makes possible getting the optimal technique of sports development and theoretical understanding of sports technique, successively adding adding new, on already acquired knowledge and skill.